Implementation of chemometrics as a Solution to detecting and preventing falsification of herbal medicines in Southeast Asia: A review - Arif Nur Ikhsan, Fella Syifa, Mabrurotul Mustafidah, Abdul Rohman& (Journal of Applied Pharmaceutical Science, 2021)
Herbal medicine has been known for centuries as one of the sophisticated traditional medicine systems and is widely used in Southeast Asia. Based on their beneficial and economical values, herbal medicines are sometimes found falsified. Chemometrics is a potential tool be developed to detect and prevent falsification. This review aimed to explore the application of chemometrics using certain chemical and biological responses for detecting the adulteration of herbal medicines in Southeast Asia. The study was carried out as a narrative review to evaluate published papers between 2000 and 2020. A total of 34 papers met the inclusion criteria and were reviewed and evaluated. Reviewed articles reveal that chemometrics successfully detected the falsification of herbal medicine with great accuracy and flexibility. Chemometrics was advantageous, practical, and cost-effective to detect adulteration and prevent falsification of herbal medicines. Nonetheless, the data published still diminish compared to the number of herbal medicines in Southeast Asia. Updated, verified, and integrated data among Southeast Asia researchers may be collected to sharpen the chemometric method. The implementation of chemometrics in Southeast Asia to detect and prevent herbal medicines was fundamental and increased the potency of herbal medicines.
Keywords: Chemometrics, authentication, identification, narrative review, Southeast Asia.